Accessing Mitochondrial Protein Import in Living Cells by Protein Microinjection - Bogorodskiy, Andrey; Okhrimenko, Ivan; Maslov, Ivan; Maliar, Nina; Burkatovskii, Dmitrii; von Ameln, Florian; Schulga, Alexey; Jakobs, Philipp; Altschmied, Joachim; Haendeler, Judith; Katranidis, Alexandros; Sorokin, Ivan; et al. (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial protein biogenesis relies almost exclusively on the expression of nuclear-encoded polypeptides. The current model postulates that most of these proteins have to be delivered to their final mitochondrial destination after their synthesis in the cytoplasm. However, the knowledge of this process remains limited due to the absence of proper experimental real-time approaches to study mitochondria in their native cellular environment. We developed a gentle microinjection procedure for fluorescent reporter proteins allowing a direct non-invasive study of protein transport in living cells. As a proof of principle, we visualized potential-dependent protein import into mitochondria inside intact cells in real-time. We validated that our approach does not distort mitochondrial morphology and preserves the endogenous expression system as well as mitochondrial protein translocation machinery. We observed that a release of nascent polypeptides chains from actively translating cellular ribosomes by puromycin strongly increased the import rate of the microinjected preprotein. This suggests that a substantial amount of mitochondrial translocase complexes was involved in co-translational protein import of endogenously expressed preproteins. Our protein microinjection method opens new possibilities to study the role of mitochondrial protein import in cell models of various pathological conditions as well as aging processes.